The Influence of Content Familiarity, Gender Difference and Proficiency Level on Reading Comprehension Performance: A Study on Malaysian Undergraduate Students in UPM (LSP International Journal, 2018)
Much research has been done on the influence of several variables individually on Reading comprehension, but the influence of these variables as a whole was not given much attention. The aim of this study was to investigate the relationship between reading comprehension as a dependent variable and three independent variables namely: gender differences, English language proficiency level and content familiarity. An additional goal was to examine the interrelation between the three independent variables. The participants were 127 male and female Malaysian students attending English language proficiency classes at the English language department in University Putra Malaysia (UPM). The study employed a quantitative approach and the data was collected through a questionnaire which was of three main parts: two reading passages (one is content-familiar and the other one is content- unfamiliar texts) and a written interview. All participants were asked to answer the whole survey and then they were classified on the basis of their proficiency level and gender. The major findings revealed that there was a direct relation between content familiarity and reading comprehension while there was an indirect relation between each of gender differences and English language proficiency level on one side and reading comprehension on the other side.